Deconstructing heterosexual privilege with new science metaphors - Tonette S. Rocco; Suzanne J. Gallagher (Adult Education Research Conference, 2006)
The purpose of the paper is to deconstruct heterosexual privilege in adult education through exploring metaphors in quantum physics and ecology. Binary heterosexist boundaries are re-envisioned and alternative adult learning and education processes are suggested.
Keywords: Sexual orientation; discrimination; quantum physics; ecology